Students' Thinking Skills in Solving HOTS Standardized Problems Based on the SOLO Taxonomy of Economics Subjects at Senior High School - Seri Ningsih; Riyo Riyadi; Sudarman Sudarman; Vitria Puri Rahayu (Journal of Economic Education and Entrepreneurship Studies, 2025)
This study aims to analyze the thinking skills of students in solving Higher Order Thinking Skills (HOTS) standardized problems based on the Structure of Observed Learning Outcomes (SOLO) taxonomy in economics subjects at the senior high school level. The research was conducted at SMA Negeri 1 Sangasanga with a qualitative descriptive approach. Participants were 31 students from class XI.3 who selected economics as their specialized subject. Data were collected using written test instruments that consisted of HOTS-oriented economic problems and were analyzed through stages of data reduction, data display, and conclusion drawing or verification. The findings revealed that students’ thinking abilities were varied and aligned with multiple levels of the SOLO taxonomy. None of the students were categorized at the Pre-structural level. A total of 8 students (26%) were at the Uni-structural level, indicating the ability to recall and identify basic concepts. Nineteen students (61%) achieved the Multi-structural level, demonstrating the ability to process multiple aspects independently. Meanwhile, 6 students (13%) reached the Relational level, showing the capacity to integrate and apply concepts holistically. These results suggest that while most students have developed foundational analytical skills, there remains a need for learning strategies that enhance deeper, integrative thinking to advance toward higher SOLO levels such as Extended Abstract.